Place-Based Philanthropy and Measuring Community Well Being in the Age of COVID-19 - Ridzi, Frank (Int J Community Wellbeing, 2021)
Place-based philanthropic organizations have long defined their value in terms of ability to improve well-being in the communities they serve. Desire to quantify and prove this impact has led such charities to be interested in and even invest in measures of community well-being. In this paper I explore how the onset of the COVID-19 pandemic has affected local philanthropy’s relationship with data and information by increasing public awareness of community data as a tool for describing rapidly changing community needs, raising expectations for an expedited connection between data analysis and action, and compelling civic leaders to engage in scenario planning. I draw on the case of Syracuse, NY to illustrate how the presence of a real time collaborative data infrastructure presents promising opportunities to address the data needs of place-based philanthropy when it comes to monitoring and acting to improve community well-being in the COVID era.